Characterization of effects of thermal-oxidative aging on styrene-butadiene rubber/silica composites with vitamin C-lanthanum complex. Issue 1 (2nd January 2016) - Zhong, Bangchao; Jia, Zhixin; Shi, Qifeng; Yang, Chao; Luo, Yuanfang; Jia, Demin
ABSTRACT: A novel rubber antioxidant, vitamin C-lanthanum complex, was prepared and applied in styrene-butadiene rubber (SBR)/silica composites. The anti-aging behavior of SBR/silica composites with vitamin C-lanthanum complex was systematically investigated by mechanical property retention after aging, oxidation induction time, exothermic enthalpies of thermal oxidation, and thermo-oxidative degradation kinetics. The highlight of this work lies in the fact that several thermal analysis techniques were successfully applied to fully evaluate the thermal-oxidative aging of SBR/silica composites and the vitamin C-lanthanum complex was found to endow SBR/silica composites with better protection against aging than commercial antioxidants, which may be beneficial for better characterization of rubber aging and fruitful for the preparation of highly aging-resistant rubber composites, respectively.